A Turbo‐Charging System‐Like Contrast Agent for MRI‐Guided STING Pathway‐Activated Cancer Immunotherapy - Bin Ren; Sihua Yan; Zongheng Li; Ya Huang; Haobin Cai; Jing Yang; Qingdeng Fan; Chunmei Chen; Fanchao Que; Guochao Wu; Lin Huang; Ruilong Zhou; et al. (Advanced Science)
Abstract To overcome the problems of Gd‐based contrast agents (GBCAs) (nephrotoxicity and brain deposition) and stimulator of interferon genes (STING) agonists (poor stability, low delivery efficiency, and potential toxicity), in this study, a Turbo‐charging system‐like GBCA is designed and constructed for magnetic resonance imaging (MRI) guided STING pathway‐activated cancer immunotherapy. Poly(acrylic acid) (PAA) is used to coordinate with Gd3+, forming a Gd/PAA macrochelate. Both Gd/PAA macrochelate and SR717 are conjugated to cystamine (CA) to obtain SR717‐CA@Gd/PAA self‐assembled nanoparticles (SAN), which are termed as Turbo S because of its similarity with the Turbo‐charging system of cars. After accumulation in tumors and internalization in tumor cells, the disulfide linkage in Turbo S undergoes a cleavage process catalyzed by glutathione (GSH), leading to the release of Gd/PAA and SR717. The released Gd/PAA gain a high r1 value (17.11 mM−1 s−1 at 7.0 T; 57.81 mM−1 s−1 at 3.0 T), indicating its strong T1 imaging capability. Turbo S with a low dosage of SR717 (8.9 mg kg−1) achieved a higher tumor immunotherapeutic efficacy than free SR717 with a high dosage (30 mg kg−1). The excellent delivery efficiency, high tumor treatment efficacy, and superior biosafety demonstrate that the Turbo S can be used as a promising candidate for tumor immunotherapy.